The robber bride - Atwood, Margaret, 1939- (Nan A. Talese/Doubleday, 1993)
One of Margaret Atwood's most unforgettable characters lurks at the center of this intricate novel like a spider in a web. The glamorous, irresistible, unscrupulous Zenia is nothing less than a fairy-tale villain in the memories of her former friends. Roz, Charis, and Tony -- university classmates decades ago -- were reunited at Zenia's funeral and have met monthly for lunch ever since, obsessively retracing the destructive swath she once cut through their lives. A brilliantly inventive fabulist, Zenia had a talent for exploiting her friends<U+2019> weaknesses, wielding intimacy as a weapon and cheating them of money, time, sympathy, and men. But one day, five years after her funeral, they are shocked to catch sight of Zenia: even her death appears to have been yet another fiction. As the three women plot to confront their larger-than-life nemesis, Atwood proves herself a gleefully acute observer of the treacherous shoals of friendship, trust, desire, and power.